GAMBARAN PENGETAHUAN IBU HAMIL TENTANG TANDA – TANDA BAHAYA KEHAMILAN DI PUSKESMAS LUBUK BUAYA PADANG TAHUN 2022-2023 - Primadella Fegita; Aldi Akbar Ripanda (Yayasan Nusantara Hasana Berdikari, 2023)
Background: Pregnancy always has risks that may cause mortality, morbidity and disability in the mother or baby. The Maternal Mortality Rate (MMR) is an indicator to determine the success of maternal health efforts. Various efforts have been made to reduce maternal mortality, one of which is by conducting regular antenatal checks to periodically check the condition of the mother and fetus. Purpose: The research aims to describe the knowledge of pregnant women about the danger signs of pregnancy at the Lubuk Buaya Padang Health Center in 2022.Methods: The scope of this research is the field of obstetric medicine. The research was conducted in November 2022 - March 2023. The type of research is descriptive. The affordable population in this study is pregnant women who come to the Lubuk Buaya Padang Health Center in 2022. Results: The highest age group for pregnant women was age not at risk (20-35 years) with 49 people (89.1%). The education of most pregnant women is high school, with 35 people (63.6%). Most of the work of pregnant women is not working as many as 40 people (72.7%). The most gravid pregnant women were multigravida as many as 35 people (63.6%). Knowledge of pregnant women about danger signs of pregnancy is mostly pregnant women with good knowledge as many as 37 people (67.3%). Conclusion: Based on the identification of the description of the knowledge of pregnant women about the danger signs of pregnancy at the Lubuk Buaya Health Center in January 2023, it is concluded that the knowledge of pregnant women about the danger signs of pregnancy is good.